Breaking misconceptions: a strategic communication model for promoting COVID-19 prevention through health protocols and vaccination in West Java Province, Indonesia - Uud Wahyudin; Hadi Suprapto Arifin; Ilham Gemiharto (Cogent Social Sciences)
This research examined public communication conducted by stakeholders to depict public perceptions of health protocols and vaccination movements during the COVID-19 pandemic. A case study was conducted to map and describe this phenomenon. The findings of this study highlight the significance of public communication in disseminating health programs during pandemics. This research contributes to a deeper understanding of public perceptions regarding public communication and health literacy. This underscores the need for comprehensive efforts in public communication, providing insights for more effective interventions. The findings suggest that governments should enhance public communication by tailoring communication methods to the characteristics of the target audience and empowering local communities. Disseminating health information literacy and promoting vaccination as a means to control the spread of COVID-19 should be prioritized through transparent and accurate data delivery and focus on communicating hope rather than panic.